Association of Joint Inflammation With Pain Sensitization in Knee Osteoarthritis: The Multicenter Osteoarthritis Study. Issue 3 (March 2016) - Neogi, Tuhina; Guermazi, Ali; Roemer, Frank; Nevitt, Michael C.; Scholz, Joachim; Arendt‐Nielsen, Lars; Woolf, Clifford; Niu, Jingbo; Bradley, Laurence A.; Quinn, Emily; Frey Law, Laura
Abstract : Objective: Pain sensitization is associated with pain severity in knee osteoarthritis (OA), but its cause in humans is not well understood. We examined whether inflammation, assessed as synovitis and effusion on magnetic resonance imaging (MRI), or mechanical load, assessed as bone marrow lesions (BMLs), was associated with sensitization in knee OA. Methods: Subjects in the Multicenter Osteoarthritis Study, a National Institutes of Health–funded cohort of persons with or at risk of knee OA, underwent radiography and MRI of the knee, and standardized quantitative sensory testing (temporal summation and pressure pain threshold [PPT]) of the wrist and patellae at baseline and 2 years later. We examined the relation of synovitis, effusion, and BMLs to temporal summation and PPT cross‐sectionally and longitudinally. Results: There were 1, 111 subjects in the study sample (mean age 67 years, mean body mass index 30 kg/m 2, 62% female). Synovitis was associated with a significant decrease in PPT at the patella (i.e., more sensitized) over 2 years (adjusted β −0.30 [95% confidence interval (95% CI) −0.52, −0.08]). Effusion was similarly associated with a decrease in PPT at the wrist (adjusted β −0.24 [95% CI −0.41, −0.08]) and with risk of incident temporal summation at the patella (adjusted OR 1.54 [95% CI 1.01, 2.36]). BMLs were not associated with either quantitative sensory testing measure. Conclusion: Inflammation, as evidenced by synovitis or effusion, is associated with pain sensitization in knee OA. In contrast, BMLs do not appear to contribute to sensitization in knee OA. Early targeting of inflammation is a reasonable strategy to test for prevention of sensitization and through this, reduction of pain severity, in knee OA.